Exposure to Korean dramas does not influence adolescent girls to consume alcoholic beverages: a case study in Medan City - Boy, Elman; Hasibuan, M Affandy (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Backrround: Korean dramas are fictional stories whose scenes have a picture of the life of Korean society itself. So that teenagers are very enthusiastic about following the style and culture in the Korean drama such as: lifestyle, fashion, Korean food and drinks. One of them is soju which is an alcoholic drink so this can cause curiosity which results in teenagers consuming alcoholic drinks. Purpose: To determine whether there is an influence of exposure to Korean dramas on the behavior of consuming alcoholic beverages among high school students in Medan city. Methods: Data collection in this study used primary data, obtained from respondents by filling out questionnaires distributed to 4 high schools in Medan city. questionnaires containing questions related to the research title that have met the inclusion and exclusion criteria with a total sample of 28 students per school. Then statistical testing was carried out with univariate and bivariate analysis.  Result: Based on the results of the study there was no relationship between exposure to Korean dramas and alcohol consumption behavior in 4 schools there were significant results SMA raksana Medan (P=0.307), SMAN 5 Medan (P=0.326), SMA Muhammadiyah 2 Medan (P=0.618). and finally MAN 2 Medan (P = 0.576). Based on gender characteristics, the sig. value of 0.000 was obtained, this value is 0.05, so it can be decided that there is a relationship between gender and alcohol consumption behavior. It was found that Korean dramas watched by high school students in Medan City did not affect their behavior in consuming alcohol, this result is the result of research from 4 schools used as research samples.